Voided Urine Sample in the Diagnosis of Prostate Cancer in Patients with Serum PSA Ranging between 2.6 to 10 ng/mL - C. Ghagane, Shridhar; Shadab, Rangrez; Nerli, R. B.; Rai, Shreyas; Thakur, Madhukar L.; Gomella, Leonard (Asian Pacific Journal of Cancer Biology, 2023)
Introduction: Prostate cancer (PCa) cells are known to be shed into the prostatic urethra and thus can be collected through a voided urine sample. In this preliminary prospective study, we have assessed the feasibility of detecting cancer of the prostate using a voided urine sample and targeting the genomic VPAC receptors in patients with lower urinary tract symptoms and a serum PSA ranging between 2.6 to 10 ng/mL. Materials & Methods: Patients ≥40 years old, with lower urinary tract symptoms and serum prostate-specific antigen (PSA) ranging between 2.6 - 10 ng/mL formed the study group. The voided urine sample was collected from all these patients for biomarker testing. All patients underwent a standard 12-core prostate biopsy. The results of the histopathological studies were then compared to the results of the urine biomarker. Results: A total of 76 male subjects presented to our hospital with lower urinary tract symptoms and a serum PSA ≥ 2.6 and ≤ 10 ng/mL. The voided urine sample was positive for malignant cells in 24/25 (96%) patients with PCa. There was one case of a false negative in this group. Histopathological examination of the core biopsy specimens was positive for malignancy in 23 (92%) cases of PCa. Conclusions: Voided urine samples can be used to diagnose PCa by targeting the VPAC receptors that are expressed on malignant cells. This test is highly sensitive and serum PSA levels or Gleason’s score have no impact on the sensitivity of this test.